CURRENT ASSET TUNNELING AND FIRM PERFORMANCE IN AN EMERGING MARKET - Sari, Ratna Candra; Baridwan, Zaki (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
This study examines the effect of current asset tunneling on firm performance from the emerging market perspective. Although tunneling activities is a common practices by businesses especially in Indonesia, there exist obstacles in the measurement of tunneling activity because it is difficult to proof the existence of such practices. In this study, we measure tunneling by using accounts receivables and develop tunneling detection criteria. In addition, this study examines the effect of tunneling on firm performance and market reaction during the announcement of the related party transaction. The study finds that from the perspective of the being-tunneled companies, receivables to related parties negatively affect the company’s profit margin. Companies which announce related party transaction indicating tunneling obtain negative abnormal return during the announcement of the related party transaction.